Respostas

2013-09-04T21:04:14-03:00
 x  -  x   = 3
4      6

m.m.c ( 4, 6) = 12                                4 , 6 I 2
                                                          2 , 3 I 2
                                                          1 , 3 I 3
  3x  - 2x   =  3                                    1, 1 I     2² X 3 = 12  
     12

  x   = 3
12

x = 3 . 12
 x =36
valeo Adriana,muito obrigada.
por nada!
2013-09-04T21:11:01-03:00
Tirando o MMC =12

3x-2x/12=3 , o 12 Dividindo Passa Multiplicando , Assim Temos :

x/12=3
x=12x3=36